Cidade-Museu: expressões espaciais e o caráter cultural - Soraia Aparecida Martins Farias (2010)
Today, the summary in metamorphose city and urban space perception through the understanding of contemporary society, taken from the expansion of capitalism and bourgeois society; it is useful to illustrate the experienced urban context. This aspect, this study has as main intention actions understanding of cultural heritage preservation of cities in the light of museums, has focused the discussion on the current socialand cultural function of the Museum in the city, while space of museum.The concepts that will permeate the entire process of preparation of contemporary knowledge of the subject, as it is today that heritage is very diverse and presents a distinct cultural expressions range. The social function of the Museum, the correlation between culturalheritage and preservation of memory and consciousness of the city while collective memory, so that museums and cities are interlocutors. The role of social memory today, as this concept has played in the social sciences, because human memory connection with social activities, inorder to allow live demonstrations of remembrance. With this fact, the conservation of remembering depends on the social environment, i.e.: it is in relationship with others that the individual can your memory work, and on the other hand, the weakening of memory derivedfrom lax occurred in relations between individual and group. The action of museums, over the years, has evolved and if modified, bringing the art as a way to associate the individual with the public space and consequently the city, in the relationship between art and architecture.